2015
DOI: 10.1007/s12034-015-0959-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silver nanoparticle on the properties of poly(methyl methacrylate) nanocomposite network made by in situ photoiniferter-mediated photopolymerization

Abstract: Here we report preparation and characterization of poly(methyl methacrylate)/silver nanoparticles (PMMA/AgNPs) nanocomposite networks prepared via in situ photoiniferter-mediated photopolymerization (in situ PMP) using tetraethylthiuram disulphide (TED) as photoiniferter and 2,2-dimethoxy-2-phenylacetophenone (DMPA) as photoinitiator. Photopolymerization was performed in the presence of allyl methacrylate, as crosslinking agent, and various amount of silver nanoparticles (AgNPs). AgNPs were synthesized via che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 34 publications
0
25
0
1
Order By: Relevance
“…[ 147–149 ] Silver nanostructures display potent antimicrobial activities that are comparable with Ag ions. [ 150 ] Silver and silver oxide (Ag 2 O) nanoparticles have diverse antibacterial applications in dentistry, [ 105,111,151 ] as scaffolds for tissue engineering [ 152,153 ] and as wound healing materials. [ 154,155 ] They have also been used as antimicrobial materials in other industries including food packaging, [ 156,157 ] drinking water disinfection, [ 158 ] and textile manufacturing.…”
Section: Metal‐based Nanocompoundsmentioning
confidence: 99%
“…[ 147–149 ] Silver nanostructures display potent antimicrobial activities that are comparable with Ag ions. [ 150 ] Silver and silver oxide (Ag 2 O) nanoparticles have diverse antibacterial applications in dentistry, [ 105,111,151 ] as scaffolds for tissue engineering [ 152,153 ] and as wound healing materials. [ 154,155 ] They have also been used as antimicrobial materials in other industries including food packaging, [ 156,157 ] drinking water disinfection, [ 158 ] and textile manufacturing.…”
Section: Metal‐based Nanocompoundsmentioning
confidence: 99%
“…Inorganic nanofillers have a large surface area which determines a high surface energy at the interface of polymer matrix, improving flexural strength; they improve hardness due to their rigidity and higher stiffness than the matrix [4] and the fracture toughness as well, because of the more uniform distribution compared to micro fillers [5]. Addition of silver nanoparticles to PMMA has several favorable effects: antimicrobial activity, increased monomer conversion, increased flexural strength and elastic modulus, improved thermal stability [6]. Tripathy showed that graphene oxide incorporation into PMMA determines improved mechanicaltensile strength, Young's modulus, strain at break, thermal and electrical properties of the material [7].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] In this work, a novel use of SLA for dental application is proposed with the aim to develop a composite occlusal bite with improved mechanical properties and antimicrobial capability. In particular, HAPfilled resin was modified with methacrylate and quaternary ammonium compound, [17][18][19] in order to provide increased adhesion of the filler with the polymer matrix and antimicrobial properties at the same time.…”
Section: Introductionmentioning
confidence: 99%